2021
DOI: 10.1001/jamaoncol.2021.1160
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Life Course Biological Age Framework to Improving the Care of Individuals With Adult Cancers

Abstract: Research on the basic mechanisms of aging and cancer will enhance our understanding of both subjects and will enable the development of new strategies for cancer prevention and treatment, as well as the optimal delivery of cancer interventions based on a person's age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 87 publications
0
46
0
Order By: Relevance
“…After matching, although age was not an independent prognostic factor in the multivariate Cox regression analysis, further survival analysis showed that patients in the old group had poorer OS when compared with the young group. While previous researchers hold the view that worse survival outcome in the elderly owed to low proportion of receiving adjuvant chemotherapy and poor preoperative nutritional status, we believed the survival disadvantage may be attribute to biological aging, which could lead to vulnerability to cancer and increase risk of cancer death ( 25 ). However, additional studies will be needed to investigate the prognostic effect of biological age in oncology research.…”
Section: Discussionmentioning
confidence: 92%
“…After matching, although age was not an independent prognostic factor in the multivariate Cox regression analysis, further survival analysis showed that patients in the old group had poorer OS when compared with the young group. While previous researchers hold the view that worse survival outcome in the elderly owed to low proportion of receiving adjuvant chemotherapy and poor preoperative nutritional status, we believed the survival disadvantage may be attribute to biological aging, which could lead to vulnerability to cancer and increase risk of cancer death ( 25 ). However, additional studies will be needed to investigate the prognostic effect of biological age in oncology research.…”
Section: Discussionmentioning
confidence: 92%
“…Muscle loss occurs to varying degrees across stages and types of disease, body weight or weight stability/ change, and leads to detrimental clinical outcomes, including lower tolerance to treatment and decreased survival [20e23,26]. In fact, low muscle mass is emerging as a clinical marker of biological age, the latter of which has been proposed as an important consideration when prescribing anti-cancer therapies [27].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] However, considerable variability exists in this trajectory of risk suggesting individual differences, or host factors, occurring possibly before cancer diagnosis exist that contribute to vulnerability in accelerated aging after cancer treatments. 12,13 Depression and its history are known host risk factors that may increase vulnerability to health declines, indicating biological aging, especially in cancer survivors. The prevalence of major depressive disorder (MDD) in cancer survivors is high, particularly in breast cancer survivors, with a prevalence nearly 4 times higher than women without a cancer history.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cancer survivors have a lower life expectancy because of recurrence or adjuvant treatment toxicities (chemotherapy, radiation) 6–9 . Together, these studies suggest that cancer and its treatments may accelerate the aging process, thereby increasing the risk of secondary health issues 10–12 . However, considerable variability exists in this trajectory of risk suggesting individual differences, or host factors, occurring possibly before cancer diagnosis exist that contribute to vulnerability in accelerated aging after cancer treatments 12,13 …”
Section: Introductionmentioning
confidence: 99%